The Association Between Obstructive Sleep Apnea and Hypertension by Race/Ethnicity in a Nationally Representative Sample. Issue 8 (10th June 2013) - Sands‐Lincoln, Megan; Grandner, Michael; Whinnery, Julia; Keenan, Brendan T.; Jackson, Nick; Gurubhagavatula, Indira
Abstract : The association between obstructive sleep apnea (OSA) and hypertension by race/ethnicity has not been well characterized in a national sample. Adult participants in the 2007–2008 National Health and Nutrition Examination Survey were reviewed by self‐report of sleep apnea diagnosis, snorting, gasping or stopping breathing during sleep, and snoring to derive whether OSA was probable (pOSA). Multivariable logistic regression determined whether pOSA predicted hypertension in the overall cohort, and by body mass index (BMI) group and ethno‐racial strata. pOSA predicted hypertension in several groups: (1) Within BMI strata, there was a significant association among overweight individuals [odds ratio [OR], 1.82; 95% confidence interval [CI], 1.26–2.62); (2) In race/ethnicity subgroups, the association was significant among Hispanic/Latinos (OR, 1.69; 95% CI, 1.13–2.53) and whites (OR, 1.40; 95% CI, 1.07–1.84); (3) In models stratified by both race/ethnicity and BMI, pOSA predicted hypertension among overweight black/African Americans (OR, 4.74; 95% CI, 1.86–12.03), overweight whites (OR, 1.65; 95% CI, 1.06–2.57), and obese Hispanic/Latino participants (OR, 2.01; 95% CI, 1.16–3.49). A simple, self‐report tool for OSA was strongly associated with hypertension, and may serve as a potential future opportunity for OSA diagnosis.